Juridical Analysis Of The Factors That Encourage Recidivism Of Narcotics Crimes : Research Study In Batam Class Iia Prison - Muhammad Adi Putra; Erniyanti Erniyanti; Ramlan Ramlan; Soerya Respationo (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
The problem of recidivist narcotics is a significant complex issue in Indonesia, including in Batam Class IIA Prison. This phenomenon raises concerns because of its negative impact on society and social stability. This study aims to analyze the juridical factors that encourage recidivism of narcotics crimes and identify obstacles in the implementation of rehabilitation programs in Batam Class IIA Prison. The research methods used are normative juridical and empirical sociology. The normative juridical method is used to analyze various laws and regulations that are the legal basis for handling recidivism, such as Law Number 35 of 2009 concerning Narcotics. Meanwhile, empirical sociological methods are used to collect data through interviews and direct observations in the field to understand the implementation of rehabilitation programs and social factors that contribute to recidivism. The results of the study show that weaknesses in the criminal justice system, lack of post-release support, social stigma, and an unsupportive social environment are the main factors that encourage recidivists. A justice system that focuses more on punishment than rehabilitation leads to a lack of effective rehabilitation programs. Minimal post-liberation support, such as difficulty finding work and housing, also contributes to high rates of recidivism. Social stigma and discrimination exacerbate the condition of ex-convicts, hindering them from reintegrating into society. An unstable social environment, especially one with easy access to narcotics, is also a driving factor for recidivism. Based on these findings, this study provides several suggestions, including increasing the number and quality of professionals in the field of rehabilitation, adjusting skills training programs to be relevant to the needs of the job market, and closer cooperation between law enforcement agencies, the government, and the community in supporting the reintegration of former prisoners. It is hoped that these suggestions can help reduce recidivism rates and increase the effectiveness of the penitentiary system in Indonesia.